Digital auscultation of the uterine artery: a measure of uteroplacental perfusion. (23rd June 2016) - Riknagel, Diana; Dinesen, Birthe; Zimmermann, Henrik; Farlie, Richard; Schmidt, Samuel; Toft, Egon; Struijk, Johannes Jan
Abstract: This observational study investigated digital auscultation for the purpose of assessing the clinical feasibility of monitoring vascular sounds in pregnancy. The study was performed at the Regional Hospital Viborg, Denmark, and included 29 pregnant women, 10 non-pregnant women and 10 male participants. Digital auscultation was performed with an electronic stethoscope bilaterally near the uterine arteries and correlated to the clinical diagnosis of preeclampsia (PE), intrauterine growth restriction (IUGR) or normal pregnancy in the group of pregnant participants. In the group of non-pregnant participants, digital auscultation was performed as control measurements in the same anatomical positions. The auscultations displayed pulse waveforms comprising systolic and diastolic periods in 20 of the 29 pregnant participants. However, in the non-pregnant and male participants, the pulse waveforms were absent. The pulsatile patterns are thus likely to originate from the arteries in relation to the pregnant uterus. In the participants displaying pulse waveforms, the presence of a dicrotic notch appeared with a sensitivity of 89% and a specificity of 100% in the discrimination of normal pregnancies ( n   =  11) from pregnancies with PE or IUGR ( n   =  9), ( p   <  0.001). This preliminary study shows the potential of identifying vascular complications during pregnancy such as preeclampsia and intrauterine growth restriction. The morphology of the derived pulse contour should be investigated and could be further developed to identify pathophysiology.